IMPROVEMENT PROPERTIES OF WHEAT FLOUR USING MICROWAVE - Ayman Soliman (Arab Universities Journal of Agricultural Sciences, 2010)
In view of balady bread in Egypt is considered as backbone in diets, accordingly, in this study wheat flour (82%) extraction treated by microwave at 2,4 and 6 minutes, that target to modify starch wheat flour by heating. The rheological properties were studied by using farinograph and extensograph apparatus. Falling number and amylose percent were determined. Balady bread samples were sensory evaluated and staling rate was evaluated. The wheat flour, crust and crumb layers of balady bread were examined by scanning electron microscope (SEM). The results of farinograph indicated that, water absorption arrival time, dough development time and dough stability increased while dough weakening decreased in wheat flour treated by microwave compared with wheat flour untreated (control). The results of extensograph revealed that, dough extensibility, resistance to extension and dough energy increased while proportional number decreased in wheat flour treated by microwave compared with control. Falling number decreased while amylose percent increased when microwave treatment increased from 2 to 6 minutes. Sensory evaluation showed slight decrease in values of both color crust and color crumb while, values of both taste and flavor slightly increased but not significantly different, meanwhile, values of crumb distribution significantly increased in balady bread samples prepared from wheat flour treated by microwave compared with balady bread prepared from untreated wheat flour (control). Wheat flour treated by microwave led to delay staling of balady bread and imilorated freshness of balady bread. The examination by scanning electron microscope (SEM) showed that average size of starch granules increased from 26.10 mm in untreated wheat flour (control) to 29.37 mm in treated wheat flour by microwave at 6 minutes.